Penyusunan Laporan Keuangan Berdasarkan SAK EMKM Pada Toko Grosir Hasanah - Rizki Fatah Maulana; Yeti Apriliawati; Jouzar Farouq Ishak (Indonesian Accounting Literacy Journal, 2022)
Hasanah Grocery Store in running its business still has not recorded and calculated accounting in accordance with SAK EMKM. The company's turnover in 2020 was less than 2 billion Rupiah, which was caused by being affected by COVID-19 and PPKM. The decline in turnover each year can result in bankruptcy of the company. Therefore, the purpose of this study was to find out how to compile the financial statements of SAK EMKM at the Hasanah Wholesale Store SMEs. In conducting this research, the writer uses descriptive qualitative research method. The data collection used is interviews, observation, and documentation. The results of this study are in the form of the Hasanah Grocery Store financial report in July 2021 in accordance with SAK EMKM which consists of a profit and loss statement, a statement of financial position and notes to financial statements.